Legal Protection for Whistleblowers in Efforts to Disclose Drug Distribution - Ridha NZ Lubis, Muhammad Rasyid; Nasution, Rasina Padeni (LEGAL BRIEF, 2025)
Knowing and explaining the legal status of whistleblowers in Indonesia. Identifying and explaining the role of informants in resolving drug trafficking crimes in Indonesia. Exploring and explaining legal protection for drug crime reporters in Indonesia. The type of research used in this article uses regulatory research based on legal provisions related to the Narcotics Law No. 35 of 2009. Using a legislative approach. This approach is carried out by examining all existing legal provisions related to the problem (legal issue). In Indonesian law, a whistleblower or crime reporter is a person who reveals corruption cases or other crimes that occur in the workplace or community. They play an important role in preventing and exposing corruption and ensuring a fair and transparent legal system. The role of informants in resolving drug trafficking cases in Indonesia is very important to increase the effectiveness of law enforcement and reduce the negative impact of these crimes on society. Reporters can act as witnesses who provide information about drug crimes to law enforcement officers, allowing these crimes to be traced and eradicated. In some cases, informants have helped find and resolve drug crimes that were previously unknown to the authorities, thereby helping to increase the effectiveness of law enforcement in addressing the problem